فاعلیة استخدام فصول جوجل الافتراضیة لتنمیة التحصیل الدراسى لوحدة دراسیة بمقرر الفهارس الآلیة لطالبات الفرقة الثالثة بقسم المکتبات والوثائق والمعلومات بکلة الآداب جامعة طنطا :دراسة تجریبیة - د. هبة فتحى دنیا (المجلة الدولية لعلوم المكتبات والمعلومات)
The purpose of this study was to examine the effects of Google Classroom fordeveloping the academic achievement of MARC 21 unit in the mechanismCatalogs course, and to identify the extent of Satisfaction of the study sample onthe use of Google classes in education. The study included 48 students in thethird year students in the Department of Libraries, Documentation andInformation at the Faculty of Arts, Tanta University during the first semester2019/2020 AD. The study used the experimental approach.Results indicate that there is a statistically significant difference at the level(0.01) between the mean scores of the students of the experimental group andthe control group for the achievement test of the MARC 21 unit in favor of theexperimental group. A statistically significant difference was found at the level(0.01) between the average scores of the students of the experimental group forthe achievement of MARC 21 unit in the pre and post measurements in favor ofthe dimensional measurement. The study sample also showed positive attitudestowards education through the Google classroom platform.